Enhancing hospital supply chain performance: A relational view and empirical test - Chen, Daniel Q.; Preston, David S.; Xia, Weidong (Journal of Operations Management, 2013)
AbstractImproving hospital supply chain performance has become increasingly important as healthcare organizations strive to improve operational efficiency and to reduce cost. In this study, we propose a research model based on a relational view, delineating the factors that influence hospital supply chain performance: trust, knowledge exchange, IT integration between the hospital and its suppliers, and hospital–supplier integration. Testing results of the research model based on data from a sample of 117 supply chain executives from U.S. hospitals show positive direct effects: (1) from trust and from IT integration to knowledge exchange respectively; (2) from knowledge exchange and from IT integration to hospital–supplier integration respectively; and (3) from hospital–supplier integration to hospital supply chain performance. The results also show the following indirect effects: (1) the influences of knowledge exchange and IT integration on hospital supply chain performance are partially and fully mediated by hospital–supplier integration, respectively and (2) the influences of trust and IT integration on hospital–supplier integration are fully and partially mediated by knowledge exchange, respectively. In addition, the results show the following moderating effects: (1) hospital system membership moderates the relationships between IT integration and knowledge exchange and between trust and knowledge exchange; (2) hospital environmental uncertainty moderates the relationship between trust and knowledge exchange; and (3) trust moderates the relationship between knowledge exchange and hospital–supplier integration. Implications of the study findings and directions for future research are discussed.